Pengembangan Model Adopsi dan Penerimaan Teknologi e-learning pada Sekolah Menengah Atas (Studi Kasus: SMA Muhammadiyah 10 GKB Gresik) - Dhiya Ulhaq Brilianty Mohamad (Fakultas Ilmu Komputer, 2025)
The development of information technology has significantly advanced education, enabling more innovative and accessible learning methods. E-learning systems offer solutions to overcome the limitations of traditional education. However, their successful implementation in secondary schools depends on how well they meet students needs and expectations, as well as the creation of a supportive learning environment. This study develops an e-learning adoption model for high school students, integrating TAM, social influence, and Facilitating Conditions from UTAUT, along with perceived mobility value, perceived enjoyment, computer self efficacy, and moderating variables of experience and gender. Data were collected from 255 students of SMA Muhammadiyah 10 using online questionnaires. The analysis followed a three-stage approach: model fit test, structural model analysis, and moderation effect analysis. The findings reveal that Perceived Mobility Value, Computer Self-Efficacy, Perceived Ease of Use, Perceived Usefulness, Perceived Enjoyment, and Behavioral Intention, which ultimately affects Actual System Use. Additionally, gender moderates the relationship between perceived ease of use, perceived usefulness and behavioral intention, while experience moderates relationships between facilitating condition and attitude. These findings contribute to the development of an empirical model for e-learning adoption among high school students
Reaploud Repository February 2026_Hasyim
Keywords: E-learning adoption model; Technology Acceptance Model; Moderating Variabel: gender and experience; High School Student